Surgical outcomes of endoscopic thyroidectomy approaches for thyroid cancer: a systematic review and network meta-analysis - Li, Xiaosong; Ding, Wei; Zhang, Hong (Frontiers in Endocrinology, 2023)
Objectives: This network meta-analysis assesses the outcomes of seven endoscopic approaches, offering valuable insights for researchers and practitioners in choosing the best method for thyroid cancer patients. Methods: A systematic literature search was conducted in the PubMed, Embase and Web of Science databases up to March 2023. The analysis included seven endoscopic approaches, with a focus on their respective outcomes through network meta-analysis. Results: This meta-analysis included 44 studies involving 8,672 patients. The axillo-bilateral breast approach (ABBA) and unilateral axillo-breast approach (UABA) showed advantages in terms of reduced operative time compared to other approaches (MD = 19.66 minutes, 95% CI = -31.66 to 70.98; MD = 30.32 minutes, 95% CI = -1.45 to 62.09, respectively). The UABA and anterior chest approach (ACA) exhibited superiority in controlling intraoperative bleeding (MD = -3.37 mL, 95% CI = -22.58 to 15.85; MD = -13.77 mL, 95% CI = -28.85 1.31, respectively). UABA and ACA also showed advantages in reducing hospital stays (MD = -0.39 days, 95% CI = -1.48 to 0.71; MD = -0.26 days, 95% CI = -1.33 to 0.81, respectively). The transoral approach (OA) yielded results comparable to those of conventional open thyroidectomy (COT) and outperformed other endoscopic surgeries with regards to lymph node retrieval and metastatic lymph node assessment. For the TG levels, no significant difference was observed between BABA and OA compared to COT. However, CBA showed significantly lower levels than COT (MD=-0.40 ng/ml, 95% CI =-0.72 to -0.09). Patients in the GUA group experienced a significant improvement in cosmetic satisfaction (MD=-2.08, 95% CI =-3.35 to -0.82). Importantly, no significant difference was observed in the incidence of surgical complications between endoscopic thyroidectomy and COT. Conclusions: Endoscopic thyroid surgery is a safe and effective choice for thyroid cancer patients. Different approaches have their advantages, allowing personalized selection based on the patient's needs. ABBA and UABA have shorter operative times, while UABA and ACA excel at controlling bleeding and shortening hospital stays. OA shows promise for lymph node assessment. These findings contribute to the growing evidence supporting endoscopic methods, expanding treatment options for thyroid cancer patients.